Análise sazonal do regime hídrico do Rio Grande do Sul no período de 1977 a 2006: impacto de sistemas meteorológicos no regime hídrico do Estado em 2006 - Silva, Morgana Vaz da (2010)
The Water regime of a region is determined by the availability of soil water (both deficiency and excess) that can be estimated with acceptable accuracy using variables such as precipitation (entry of water into the ground) and evapotranspiration (output of water from the soil) through a system of water balance. The aim of this study was to determine and analyze the seasonal climatological water balance in the northern half and southern half of Rio Grande do Sul (RS) from 1977 to 2006, as RS has had a significant spatial variability of annual precipitation since in the southern half is lower than the Northern Half of the state. Specifically, it was analyzed the impact of weather systems on the water regime of RS in 2006. It has been used for the calculation of water balance, monthly data of average temperature and precipitation from 1977 to 2006, which was obtained from the National Institute of Meteorology - INMET (8th District of Meteorology) from 16 meteorological stations located in different ecoclimatic regions of the state. To calculate the water balance it was been used the method proposed by Thornthwaite and Mather (1955) and to calculate the evapotranspiration, the method of Thornthwaite (1948) was used the data from Bulletins of Climate Analysis from database of civil defense of RS and satellite images GOES-12 (Geostationary Operational Environmental Satellite) provided by the Center for Weather Forecasting and Climate Studies located at the National Institute for Space Research - CPTEC / INPE. The results for the study period (1977 to 2006) showed that the distribution of precipitation in RS was fairly uniform across the four periods of the year with record volumes of rainfall in the northern half of the state. It may be noted that the North Half of RS has presented over water throughout the year due to higher rainfall associated with lower evaporative rates. In the south, water deficits in JFM and OND has been observed, but these have been less than the excess water, so there is lack of water. In 2006 the northern half of RS, lack of water has not occurred, despite the occurrence of water deficits in the quarters of JFM, AMJ and OND. In the southern half in 2006, the reduced availability of water and increased water stress in relation to normal conditions have caused water shortages in JFM and OND on the coast. Factors that contributed to the occurrence of excess water above the water deficit during 2006 in the North Half and water shortages in the south of RS in JFM and OND on the coast, have been: highest frequency of Weather and Climate System event with severe weather conditions in the northern half of RS related to the southern half; the lowest frequency of Frontal System this year in the south of RS related to the climate normal period from 1977 to 2006 and the role of ENSO whose configuration in 2006 led to drought in southern Brazil, and therefore precipitation below normal in all quarters year.